An exploration of the initiation time and patient selection of PD-1 inhibitors/PD-1 inhibitors combined with chemotherapy as salvage therapy in R/R DLBCL patients after anti-CD19-CAR T-cell therapy - Xin Li; Juan Mu; Jia Wang; Qing Li; Yili Jiang; Jingyi Li; Qi Deng (Cell Transplantation)
A significant proportion of patients with relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL) exhibit no response to chimeric antigen receptor (CAR) T-cell therapy or suffer from disease progression thereafter. This study investigated the efficacy and safety of salvage therapy with PD-1 inhibitor-based combination treatment and the patient selection after their CAR T-cell therapy. Twenty-one patients with R/R DLBCL and a high tumor burden were treated with CAR T-cell therapy, a treatment that has shown promising results in clinical trials and has been approved by the Food and Drug Administration (FDA) for use in DLBCL. Patients who achieved complete response (CR) with the CAR T-cell therapy received salvage therapy when their disease progressed again. Patients who obtained partial response (PR) or stable disease (SD) with the CAR T-cell therapy received salvage therapy immediately. Salvage therapy consisted of single PD-1 inhibitors or PD-1 inhibitors combined with chemotherapy. We observed the overall response rate (ORR), overall survival (OS), CAR T-cell amplification, the expression of PD-1, CD3+ T cells, cytokines, and the adverse events. For instance, in a clinical trial of LCAR-B38M CAR T-cell therapy, an 88% ORR was observed, with 74% of patients achieving CR and a median duration of response (DOR) of 16 months. The ORR and CR of the salvage therapy were 28.57% and 19.05%, respectively. The ORR and CR were 38.46% and 30.77% in the 13 patients who achieved PR/SD with the CAR T-cell therapy and received salvage therapy 2 months after CAR T-cell infusion. But the ORR and CR were only 12.5% and 0%, respectively, in patients who achieved CR with the CAR T-cell therapy and received salvage therapy when they experienced disease re-progression. The ratio of CAR-T cells on day 7/day 14 was lower in the PR in CAR-T (effective to PD-1) group. Before salvage therapy, the percentage of CD3+ T cells was higher in the PR in CAR-T (effective to PD-1) group. There was no difference in the Common Terminology Criteria for Adverse Events (CTCAE) grades among the four groups in the salvage therapy. PD-1 inhibitor-based salvage therapy in patients with R/R DLBCL following the CAR T-cell therapy could be an effective and safe treatment, especially in patients who achieved PR after the CAR T-cell therapy and received this salvage therapy immediately. Trial registration number : ChiCTR1800019622 and ChiCTR1900025310